Quantification of the purinergic P2X7 receptor with [11C]SMW139 improves through correction for brain-penetrating radiometabolites. Issue 2 (February 2023) - Brumberg, Joachim; Aarnio, Richard; Forsberg, Anton; Marjamäki, Päivi; Kerstens, Vera; Moein, Mohammad M; Nag, Sangram; Wahlroos, Saara; Kassiou, Michael; Windhorst, Albert D; Halldin, Christer; Haaparanta-Solin, Merja; et al.
The membrane-based purinergic 7 receptor (P2X7 R) is expressed on activated microglia and the target of the radioligand [ 11 C]SMW139 for in vivo assessment of neuroinflammation. This study investigated the contribution of radiolabelled metabolites which potentially affect its quantification. Ex vivo high-performance liquid chromatography with a radio detector (radioHPLC) was used to evaluate the parent and radiometabolite fractions of [ 11 C]SMW139 in the brain and plasma of eleven mice. Twelve healthy humans underwent 90-min [ 11 C]SMW139 brain PET with arterial blood sampling and radiometabolite analysis. The volume of distribution was estimated by using one- and two- tissue compartment (TCM) modeling with single ( V T ) and dual ( V Tp ) input functions. RadioHPLC showed three major groups of radiometabolite peaks with increasing concentrations in the plasma of all mice and humans. Two radiometabolite peaks were also visible in mice brain homogenates and therefore considered for dual input modeling in humans. 2TCM with single input function provided V T estimates with a wide range (0.10–10.74) and high coefficient of variation (COV: 159.9%), whereas dual input function model showed a narrow range of V Tp estimates (0.04–0.24; COV: 33.3%). In conclusion, compartment modeling with correction for brain-penetrant radiometabolites improves the in vivo quantification of [ 11 C]SMW139 binding to P2X7 R in the human brain.